Do Public and Private Firms Behave Differently? An Examination of Investment in the Chemical Industry - Sheen, Albert (Journal of Financial and Quantitative Analysis, 2020)
I compare the U.S. capacity expansion decisions of public and private producers of 7 commodity chemicals from 1989 to 2006. I find that private firms invest differently than public firms. Private firms are more likely than public firms to increase capacity prior to a positive demand shock (an increase in price and quantity) and less likely to increase capacity before a negative demand shock. Potential mechanisms include public firm overextrapolation of past demand shocks and agency problems arising from greater separation between ownership and control.